PERFORMANCE OF MULTICUT FORAGE SORGHUM UNDER VARIOUS SOWING METHODS AND NITROGEN APPLICATION RATES - M. Afzal; A. U. H. Ahmad; S. I. Zamir; F. Khalid; A. U. Mohsin; S. M. W. Gillani (Journal of Animal and Plant Sciences, 2013)
A field experiment was conducted to assess the different nitrogen levels and sowing methods on multicut sorghum at University of Agriculture, Faisalabad. Replicated three times the experiment was laid out in randomized complete block design (RCBD) with split plot arrangements with a plot size of 2.7m x 6m. The experimental treatments were viz. 0, 57.5, 28.75, and 45 kg N/ha N1, N2, N3, N4 respectively at sowing and after each cut and two sowing methods i.e. broadcast and drill sowing with 30 cm apart rows. The growth, yield and quality parameters differed significantly among the different nitrogen levels and sowing methods. The observations including plant height, number of leaves per plant, stem diameter, leaf area per plant, fresh weight per plant, dry weight per plant, total green forage yield, total dry matter yield, crude protein and ash % in three cuttings showed that drill sowing at 30 cm apart rows with nitrogen level of 57.5 kg ha-1 enhanced significantly the growth and yield of sorghum compared to the other treatments under the environmental conditions of Faisalabad.
Keywords: Sorghum forage; Nitrogen; Sowing Methods; Yield; Quality